Young plasma ameliorates aging-related acute brain injury after intracerebral hemorrhage. Issue 5 (17th May 2019) - Yuan, Jun-Jie; Zhang, Qin; Gong, Chang-Xiong; Wang, Fa-Xiang; Huang, Jia-Cheng; Yang, Guo-Qiang; Liu, Liang; Zhou, Kai; Xu, Rui; Chen, Qiong; Zhou, Yu; Xiong, Xiao-Yi; et al.
Abstract : Aging has been shown to contribute to both the declined biofunctions of aging brain and aggravation of acute brain damage, and the former could be reversed by young plasma. These results suggest that young plasma treatment may also reduce the acute brain damage induced by intracerebral hemorrhage (ICH). In the present study, we first found that the administration of young plasma significantly reduced the mortality and neurological deficit score in aging ICH rodents, which might be due to the decreased brain water content, damaged neural cells, and increased survival neurons around the perihematomal brain tissues. Then, proteomics analysis was used to screen out the potential neuroprotective circulating factors and the results showed that many factors were changed in health human plasma among young, adult, and old population. Among these significantly changed factors, the plasma insulin-like growth factor 1 (IGF-1) level was significantly decreased with age, which was further confirmed both in human and rats detected by ELISA. Additionally, the brain IGF-1 protein level in aging ICH rats was markedly decreased when compared with young rats. Interestingly, the relative decreased brain IGF-1 level was reversed by the treatment of young plasma in aging ICH rats, while the mRNA level was non-significantly changed. Furthermore, the IGF-1 administration significantly ameliorated the acute brain injury in aging ICH rats. These results indicated that young circulating factors, like IGF-1, may enter brain tissues to exert neuroprotective effects, and young plasma may be considered as a novel therapeutic approach for the clinical treatment of aging-related acute brain injury.